2014
DOI: 10.7162/s1809-48722012000100006
|View full text |Cite
|
Sign up to set email alerts
|

Age at the diagnosis and in the beginning of intervention from hearing impaired children, in a public Brazilian hearing health service

Abstract: Summary Introduction:?The earlier the diagnosis and the intervention from the hearing impairment less will be the impact for the development of cognitive abilities, hearing and of speech from the child. Objective:?Characterize the age in the diagnosis and the beginning of intervention of the hearing loss and the accompaniment of the assisted children in a public Brazillian hearing health service ? Espa?o Reouvir from the Clinicas Hospital from the Medical School from the University of S?o Paulo. Method:?Ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 15 publications
1
12
0
2
Order By: Relevance
“…These data corroborate the study which concluded that children from developing countries appear for intervention, even after late diagnosis, hindering the development of auditory, cognitive and language skills 16 .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These data corroborate the study which concluded that children from developing countries appear for intervention, even after late diagnosis, hindering the development of auditory, cognitive and language skills 16 .…”
Section: Discussionsupporting
confidence: 81%
“…Literature highlights the importance of early diagnosis and intervention due to the great impact that may result in the early years of life, considering that this is the period of greater plasticity of the central nervous system 10,16 . Still at this stage of life, the child uses his hearing for the initial contact with the oral sounds, thus the phono-articulatory proprioception provides the development of feedback-auditory, preparatory for the improvement of one's own speech 17-19 . Moreover, there are other factors presented in literature and experienced in clinical practice as a preponderant for the development of hearing (auditory) and oral communication skills, such as: degree of hearing loss, stability of the degree of this loss, adaptation of the auditory technological resource and aural rehabilitation [20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…Sensorineural hearing loss had the greatest prevalence, which was also observed in public hearing health programs in Santa Maria (RS) 15 , Montes Claros 17 , Florianópolis (SC) 22 , Ribeirão Preto (SP) 19 , São Paulo (SP) 18 and a predominance of moderate hearing loss is supported by studies from Monte Negro (RO) 4 , Santa 23 , a study also found that, due to insufficient financial resources, this population was not able to utilize PSAP until the establishment of Hearing Health Care Services.…”
Section: Discussionmentioning
confidence: 99%
“…The low number of children evaluated may indicate late diagnosis or intervention, which also occurs in other municipalities such as São Paulo (SP) 18 and Ribeirão Preto (SP) 19 . However, the importance of early detection and the need for investments in the active search for children with the State Newborn Hearing Screening Program.…”
Section: Discussionmentioning
confidence: 99%
“…What calls attention and also meets the observed in other studies (18,19) is that, although big part of these children has a pediatrician support, a few were the cases in which this professional looks at hearing aspects (7.2%). In the cases which there was no suspicion of hearing loss (n=14), all the subjects had losses categorized as normal/mild/moderate degrees, what justifies the absence of the suspicion, seen that the hearing loss can remain undetectable to the parents/teachers for a prolonged period of time (20,21) .…”
Section: Discussionmentioning
confidence: 99%